Understanding the Domestic Rupture in Forensic Psychiatric Nursing Practice. (January 2014) - Jacob, Jean Daniel
The objective of this article is to examine the tensions that exist between care and custody in correctional environments by presenting the (im)possibilities of psychiatric nursing practice within this context. The analysis will be guided by empirical data obtained from a qualitative research conducted in a correctional setting. Semistructured interviews with nurses were conducted and used as the primary source of data for analysis. This article will explore the contextual characteristics of psychiatric nursing practice in correctional settings, describe the alienating effects of this context on nursing practice, theorize nurses' experience using Festinger's theory on cognitive dissonance, and, finally, explore how some nurses engage in the reconstruction of their care to counter the effects of working in correctional settings.